(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Learning a foreign language can be a challenging task, but incorporating creative musical activities into language learning has shown significant benefits. This article explores the importance of using music as a tool for language acquisition and provides insights into various methods of application.